2010
DOI: 10.5012/bkcs.2010.31.01.168
|View full text |Cite
|
Sign up to set email alerts
|

Study of 7-Methylguanine on pKaValues by Using Density Functional Theoretical Method

Abstract: Methylation of DNA by endogenous methylating agents generates a variety of genotoxic adducts.1 The N7 position of guanine is known as the most nucleophilic site within the heterocyclic bases of DNA.2 Accordingly, N7-methylguanine (7MeG) is the one of the most prevailing forms of the methylated guanine. 7MeG is also generated by methylation in order to be used as a probe of protein-DNA interactions and DNA sequencing. Recently, a DNA double helical structure of a 25-mer containing a 7MeG was reported, which rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Moreover, 7mG has two macroscopic pKa values: the first pKa value is 4.44 and the second one is 10.75 according to Hwang et al. 35. We have found a slope change at the plot peak potential versus pH at a pH value below 4.0, as depicted in figure S3.…”
Section: Resultssupporting
confidence: 60%
“…Moreover, 7mG has two macroscopic pKa values: the first pKa value is 4.44 and the second one is 10.75 according to Hwang et al. 35. We have found a slope change at the plot peak potential versus pH at a pH value below 4.0, as depicted in figure S3.…”
Section: Resultssupporting
confidence: 60%
“…This indicates that an equal amount of protons and electrons is involved in electrode reaction as well. However, it is worth noting that at pH 4.19, SWV response deviates from the linear trend attributed to the pKa1 of the substance near 4.4 [49]. By contrast, Brotons et al [27] reported a value of pH dependence for the electro-oxidation of 7-mG at screen printed graphite electrodes (SPGE) of 27 mV pH -1 within a pH range of 3 and 9 in phosphate buffer solutions.…”
Section: Effect Of Ph On the Electrochemical 7-mg Swv Response At Bddmentioning
confidence: 99%